Dental health and diet in early medieval Ireland. Issue 9 (September 2015) - Novak, Mario
Highlights Six attributes of oral health in the early medieval Irish are presented. Men show significantly higher prevalence of abscesses, heavy wear and alveolar bone resorption. Women exhibit significantly higher prevalence of calculus. Dental wear associated with habitual activities was recorded in two females. The diet of the early Irish was rich in carbohydrates with sporadic use of meat.